Simple reaction time as an indicator of lightness contrast effect mechanisms - possibilities and limitations - Ivanec, Dragutin (Array, 2005)
Best known example of contextual effect is simultaneous lightness contrast. Differences in lightness perception of surfaces with objectively same lightness, depending on the background have dominantly been interpreted by processes of lateral inhibition (peripheral mechanisms). However, recent studies suggest that lateral inhibition processes are not sufficient in explaining simultaneous contrast effect. These studies indicate that lightness perception in simultaneous contrast effect also depends on assimilation processes as well as on higher cognitive process related to perceptual belongingness. The aim of this study was to examine the possibility of using simple reaction time (RT) as an indicator of potential lightness contras effect mechanism. RT could be indicator of peripheral (retinal) level of processing stimulus intensity. Namely, RT is susceptible to stimulus intensity – increase in stimulus intensity leads to decrease in RT. If changes in RT are consistent with changes on perceived intensity level in situation of simultaneous lightness contrast, that could suggest the importance of retinal processes in lightness contrast effect mechanism. RT on surface (stimulus) of the same lightness on different lightness background was measured. Results indicated that RT is linked to simultaneous contrast. RT to same stimulus differs significantly, depending on the background, and is consistent with perceived intensity. RT on same stimulus intensity on darker background is significantly shorter compared to situation where the background is brighter. That suggests that differences in perception of lightness intensity in the figure of lightness contrast are mediated by retinal processes. However, obtained results can not confirm the hypothesis of lateral inhibition as an unequivocal mechanism of simultaneous contrast. Methodological problem in the use of RT is that RT is also susceptible to stimuli contrast and not only to stimulus intensity. For example, RT for black stimulus on white background is the same as for the white stimulus on black background, and the energetic magnitude for white stimulus is significantly higher that for the black one.